The effect of compost made of sheep manure on the first cut of a semi-natural grassland - Díaz Fernández, Daniel; Csízi, István (Acta Agraria Debreceniensis, 2018)
In an experiment, two types of compost were tested on natural grassland in order to improve the productivity of a natural sward on solonetz soil. Both composts were made of on-farm produced sheep manure, but the second one was enriched in phosphorus. These fertilizers/composts are officially authorized and can be applied in organic farming. Zero application and three rates of fertilizer were tested (10 t ha-1, 20 t ha-1, 30 t ha-1) on 30 m2 experimental plots wit four replications. Dry matter, crude protein and net energy content for maintenance were measured and determined and their yields per unit area were calculated. We found that all the treated plots produced significantly higher yield than the control ones, and in some cases the yields were almost three times higher. However, the optimal compost dose varied, depending on the examined parameter. Based on the evaluation of the experiment results along with rainfall data, it was concluded that, with higher precipitation, the positive effect of the compost application was bigger. The difference between the natural and enriched compost is remarkable, but it has to be mentioned that even the natural compost showed good results; therefore, it is also effective in improving the fertility of grassland.